Kemampuan Prediktif Teori Akuntansi Positif Terhadap Praktik dan Riset Akuntansi: Sebuah Kajian Konseptual - Eko Suyono (JBIMA (Jurnal Bisnis dan Manajemen), 2018)
This study intends to evaluate the predictive value of the positive accounting theory approach. Using the internet and library research, this study sought to collect research literature using the positive accounting theory approach from the early to the current period. After a careful and in-depth review of the extant literature using the positive accounting theory approach, this study concludes that positive accounting theory has a good predictive value for current and future practices and research in accounting besides there are several critics on the positive accounting theory methodology and philosophy. Therefore, the future studies will contribute to solving the positive accounting theory problems.